2003
DOI: 10.1093/jb/mvg111
|View full text |Cite
|
Sign up to set email alerts
|

Silver Ion Induces a Cyclosporine A-Insensitive Permeability Transition in Rat Liver Mitochondria and Release of Apoptogenic Cytochrome c

Abstract: Various reagents are known to open the mitochondrial permeability pore (PTP) and induce a permeability transition (PT), releasing apoptogenic proteins from the intermembrane space and triggering apoptosis. In this study, we examined the effect of Ag(+), a known cytotoxic sulfhydryl-reactive heavy metal, on isolated rat liver mitochondria. The following results were obtained: (1) Upon addition, Ag(+) instantly induced mitochondrial swelling and acceleration of respiration. (2) Cyclosporine A, a specific inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 26 publications
6
70
0
1
Order By: Relevance
“…The cell viability assays shows that A549 cells have significant inhibitory effect of AgNPs and are more sensitive than L132 lung normal cells (Figure 11). Our studies are consistent with previous studies which show that AgNP exposure could induce the changes of cell shape, reduce cell viability, increase LDH release, and finally result in cell apoptosis and necrosis [48,51,53,[109][110][111]. Effect of AgNPs on cell viability of L 132 and A549 cells.…”
Section: Effect Of Agnps On Cell Viability Of L132 and A549 Cellssupporting
confidence: 92%
“…The cell viability assays shows that A549 cells have significant inhibitory effect of AgNPs and are more sensitive than L132 lung normal cells (Figure 11). Our studies are consistent with previous studies which show that AgNP exposure could induce the changes of cell shape, reduce cell viability, increase LDH release, and finally result in cell apoptosis and necrosis [48,51,53,[109][110][111]. Effect of AgNPs on cell viability of L 132 and A549 cells.…”
Section: Effect Of Agnps On Cell Viability Of L132 and A549 Cellssupporting
confidence: 92%
“…Possibly, other hydraulic permeability pathways in the IMM may also be affected by Cd 2ϩ . Thus we show that Cd 2ϩ can alter IMM permeability pathways and induce the release of Cyt c by processes that are independent of the PTP, which confirms that PTP opening is not the only mechanism underlying mitochondrial swelling (1,2,20,45). At the present stage, we can only speculate about the mechanism of Cd 2ϩ -induced activation of AQP8, but cysteine residues are important for AQP channel function and inhibition by Hg 2ϩ (44) and could be involved in the alteration of the AQP8-associated permeability of the membrane by Cd 2ϩ .…”
Section: How Does CD 2ϩ Affect Permeability Of the Imm?supporting
confidence: 69%
“…Accordingly, it has been suggested that Cd 2ϩ induces the release of Cyt c by modifying the interaction of members of the Bcl-2 protein family with mitochondrial membranes (27,28,35) and/or by activation of the permeability transition pore (PTP) (13,36). However, there is accumulating evidence that cytotoxic compounds may alter mitochondrial membrane permeability and the release of Cyt c by processes that are independent of these classic mechanisms (1,2,20,45). Thus the molecular processes underlying Cd 2ϩ -induced mitochondrial damage and dysfunction that are associated with Cyt c release still await clarification.…”
mentioning
confidence: 99%
“…As a result, the PT and the release of cytochrome c were found to be induced not only by Ca 2ϩ but also by other agents (7)(8)(9). We also found that copper-o-phenanthroline (10), metal ions (11), and cyanine dyes (12,13) induced this PT and the release of cytochrome c from mitochondria. Furthermore we reported that valinomycin, known as a potassium-selective ionophore, also induces the release of cytochrome c from mitochondria but without the induction of PT (14).…”
mentioning
confidence: 59%